Assessment of the molecular cytogenetic, morphometric and biochemical parameters of Deschampsia antarctica from its southern range limit in maritime Antarctic - Daria Navrotska; Igor Andreev; Alexander Betekhtin; Magdalena Rojek; Ivan Parnikoza; Ganna Myryuta; Oksana Poronnik; Natalia Miryuta; Joanna Szymanowska-Pułka; Volodymyr Grakhov; Roman Ivannikov; Robert Hasterok; et al. (Polish Polar Research, 2018)
Different chromosomal forms of Deschampsia antarctica Desv. (Poaceae), including diploids (2n=26), hypotriploid (2n=36–38) and a genotype with an occasional occurrence of B chromosome (2n=26+0-1B) that originated from southern marginal populations (Argentine Islands region, maritime Antarctic) were studied using molecular cytogenetic, morphometric and biochemical methods. FISH analysis revealed variations in the number of rDNA sites between the diploid and hypotriploid plants. The genome size varied among plants with a different chromosome number and was on average 10.88 pg/2C for diploids and 16.46 pg/2C for hypotriploid. The mean values of leaf length of plants grown in vitro varied within a range of 5.23–9.56 cm. The total phenolic content ranged from 51.10 to 105.40 mg/g, and the total flavonoid content ranged from 1.22 to 4.67 mg/g. The amount of phenolic compounds did not differ significantly between the genotypes, while a variation in the flavonoid content was observed for L59 and DAR12. The diploids did not differ significantly among each other in terms of the number of rDNA loci, but differed slightly in their genome size. The individuals of DAR12 carrying B chromosome were similar to other diploids in terms of their genome size, but statistically differed in leaf length. The hypotriploid had both a greater number of rDNA sites and a larger genome size. No statistical correlations were observed between the genome size and leaf length or genome size and accumulation of phenolic and flavonoid compounds. The results of this study suggest that D. antarctica plants from the southern edge of the range are characterised by the heterogeneity of the studied parameters.